A National Population Study of the Co-Occurrence of Multiple Long-Term Conditions in People With Multimorbidity, Denmark, 2013 - Karina Friis, PhD; Marie Hauge Pedersen, MSc; Finn Breinholt Larsen, MSc (Centers for Disease Control and Prevention, 2016)
The objective of this study was to describe the prevalence of pairwise combinations of 17 long-term conditions. Data were obtained from a national, representative population-based study including 162,283 Danish citizens aged 16 years or older. We calculated the prevalence of each long-term condition given the presence of another long-term condition. Compared with the general population, people with angina pectoris had more than twice the odds of having 12 of the 16 other long-term conditions, and inversely, people with cancer, tinnitus, or cataracts did not have notably higher odds for any of the other long-term conditions.